Patterns of global terrorism 1985-2005 : U.S. Department of State reports with supplementary documents and statistics - Sabasteanski, Anna, 1958- (Gale virtual reference library, 2005)
"A comprehensive reference--designed for military, government, and security professionals as well as students of politics, international relations, history, public policy, homeland security, foreign policy, emergency management, and military science--that collates the U.S. Department of State reports on terrorism, Patterns of Global Terrorism, with additional analytical and statistical material"--Provided by publisher